Work of Integrated Departments as Exemplified by the Department of Ukrainian Studies - Pomazan , I. (New Collegium, 2021)
The article is devoted to the review of the experience of the Department of Ukrainian Studies of Kharkiv University of Humanities “People’s Ukrainian Academy” as an integrated structural unit of an innovative educational institution operating on the principles of continuous education. Considerable attention is paid, in particular, to the practical implementation of this concept in educational activities (the organization of study hours, the development of basic integrated programs in the Ukrainian Language, Ukrainian Literature and Foreign Literature, which cover teaching in both secondary and higher schools), research and educational work on the formation of the modern specialist as an intellectual and worthy individual with his own civic position. When reviewing the educational and methodological practices of the department, especially highlighted are integrated programs developed by the department academic staff, namely, the integrated programs on the Ukrainian Language, Ukrainian Literature, as well as the program on the History of Foreign Literature. The principles of drawing up these programs are set out in accordance with the task of the most effective implementation of both vertical (from secondary to higher school) and horizontal (interdisciplinaryt) integration. Special attention is paid to the technologies of online education, in particular, online courses developed at the department as a promising algorithm for the effective organization of the educational process. The multi-vector educational work carried out by the department staff in cooperation with other structural divisions of People’s Ukrainian Academy is also in the focus of the author’s attention. The participation of the department staff in nation-wide educational projects such as External Independent Evaluation in the Ukrainian Language and Literature has also been emphasized. When analyzing each component of the structural block, emphasis is put on the essence of its integrated format and its significance for the successful implementation of the concept of the complex of continuing education, in general, and the formation of a fully rounded personality that will feel confident in modern world, in particular.